2020
DOI: 10.3390/brainsci10060399
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonian Syndrome with Frontal Lobe Involvement and Anti-Glycine Receptor Antibodies

Abstract: Background: Atypical Parkinsonian syndromes with prominent frontal lobe involvement can occur in the 4R-taupathies progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD). Secondary forms of movement disorders may occur in the context of autoimmune encephalitis with antineuronal antibodies, such as anti-glycine receptor (anti-GlyR) antibodies, which are typically associated with Stiff-Person spectrum syndrome, or progressive encephalomyelitis with rigidity and myoclonus. Overlaps between neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Limbic encephalitis, encephalitis or encephalopathy are less often reported in conjunction with glycine-receptor antibodies in these studies. One of our patients suffers from akinetic rigidity syndrome, in line with a report of a Parkinson's syndrome involving frontal lobe atrophy and glycine-receptor antibodies (14). However, recent research showed novel features in a subgroup of glycine-receptor antibody-positive patients describing various visual dysfunction phenomena (15).…”
Section: Discussionsupporting
confidence: 86%
“…Limbic encephalitis, encephalitis or encephalopathy are less often reported in conjunction with glycine-receptor antibodies in these studies. One of our patients suffers from akinetic rigidity syndrome, in line with a report of a Parkinson's syndrome involving frontal lobe atrophy and glycine-receptor antibodies (14). However, recent research showed novel features in a subgroup of glycine-receptor antibody-positive patients describing various visual dysfunction phenomena (15).…”
Section: Discussionsupporting
confidence: 86%
“…A 63-year-old woman with atypical parkinsonism with the frontal syndrome was presented by Endres et al [ 11 ]. At the age of 60, her symptoms started with insomnia and, in a year, progressed into personality changes with depression and delusions followed by severe cognitive impairment and postural unsteadiness, and parkinsonian symptoms in the left upper extremity.…”
Section: Discussionmentioning
confidence: 99%